Indirect Taxes, Subsidies and the Cost-of-Living Index. - Barna, Tibor (Review of Economic Studies, 1942)
Journal Article Indirect Taxes, Subsidies and the Cost-of-Living Index Get access Tibor Barna Tibor Barna London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 10, Issue 1, Winter 1942, Pages 53–61, https://doi.org/10.2307/2967495 Published: 01 December 1942